Closed-loop control of BLDC motor using Hall effect sensors - B. Ramesh; Kalagotla Chenchireddy; Baddam Nikitha Reddy; Bellamkonda Siddharth; Chelmala Vinay Kumar; Putta Manojkumar (International Journal of Applied Power Engineering (IJAPE), 2023)
Due to its key advantages of top performance, strong torque, and simple volume, brushless direct current (BLDC) motors are now extensively employed in a variety of industrial sectors, including the automotive industry, robotics, and electrical vehicles. Yet, in some circumstances, it can be challenging to use speed control techniques for specific devices. The major goal of this work is to use a proportional integral derivative (PID) converter to regulate the speed characteristics of BLDC. PID converter is preferred over all other converters because of its straightforward design and straightforward implementation. Using MATLAB simulation results are verified at different reference speed changing conditions, the motor input current and back electromotive force (EMF) values are verified. The speed and torque characteristics are verified during steady and transient state conduction.